Upaya Meningkatkan Hasil Belajar Materi Asmaul Husna Menggunaka Metode Diskusi - Bonniadi, Bonniadi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research aims to improve students' learning outcomes in the Asmaul Husna material by using the discussion method. The study was conducted in the 4th-grade class of SD 16 Batang Tuhur, Dua Koto District, Pasaman Regency, involving 10 students as the sample. The research was carried out through two action cycles, where the first cycle showed that most students achieved mastery learning, but some students were still unable to meet the minimum criteria. In the second cycle, improvements were made by using audiovisual media and more interactive discussion activities, resulting in significant improvement, with all students achieving mastery learning. The research findings indicate that the application of the discussion method combined with engaging media can enhance students' understanding and encourage active participation in learning.